(untitled) - Roberts, Ron (San Francisco, 2007)
In Learn-o-grams Ron Roberts presents a wealth of energizing and entertaining puzzles designed for training sessions that are a combination of words, letters, and pictures that represent a more complex word or phrase. To solve these puzzles participants must think outside the box, stretch their imagination, and use both the left and right side of the brain. Learn-o-grams game book is unique and adds a dash of excitement to training sessions, meeting openers, energizer, breaks, topical transitions, and closers. These fun-filled puzzles are also ideal for teaching skills such as communication, leadership and risk taking, teamwork and group synergy, strategic planning and execution, process improvement and accelerated learning, as well as systems thinking.
Keywords: Educational games,Puzzles,Trò chơi giáo dục,Đố vui